Analisis Antrian Dan Tundaan Ruas Jalan Urip Sumoharjo Akibat Putar Balik Arah (U-Turn) Depan Mall Nipah - Lea Patti Dalipang; Rais Rachman; Ari Kusuma (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
One of the things that affect when doing the reverse movement is the speed of the vehicle where the vehicle will experience a slowdown or stop (delay). This slowdown will affect the flow of traffic in the same direction. In certain vehicles, to make a U-turn movement you cannot directly make a rotation because the condition of the vehicle does not have sufficient turning radius, so that it will interfere with other vehicles and even stop both from the same direction and from the opposite direction that will be traversed. Therefore, research was carried out which aims to analyze the volume of U-Turn traffic, determine the length of the queue when making a U-Turn, and find out the delay time when making a U-Turn. To analyze the data, the PKJI 2014 method was used. From the results of this study, the traffic volume was 4356 cur/hour for the Maros-Makassar direction and 5776 for the Makassar-Maros direction, the highest queue length when making a U-Turn in front of Nipah Mall was 35 meters for for the direction of Maros - Makassar and 143 meters for the direction of Makassar - Maros, and the highest delay due to U-Turn is 4.21 seconds for the direction of Maros - Makassar and 7.17 seconds for the direction of Makassar - Maros.